2012
DOI: 10.1038/ejhg.2012.239
|View full text |Cite
|
Sign up to set email alerts
|

Two novel mutations of the GTP cyclohydrolase 1 gene and genotype–phenotype correlation in Chinese Dopa-responsive dystonia patients

Abstract: The most common form of Dopa-responsive dystonia (DRD) is caused by heterozygous mutations in the GTP cyclohydrolase I (GCH1) gene. We screened two unrelated, DRD-symptomatic Chinese Han individuals, for GCH1 gene mutations by direct sequencing. As the clinical manifestations of DRD are highly variable, we also explored the association between genotype and phenotype in all Chinese DRD patients reported so far in the literature, comprising 62 DRD-affected patients from 36 Chinese families. Two novel missense mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…For PCDD, AR-GTPCHD, DHPRD, and PTPSD, there are no consistent reports on genotype-phenotype correlation. For AD-GTPCHD, there is certain heterogeneity: Some publications discuss and exclude genotypephenotype correlation [35,36]. Others describe different large heterozygous GCH1 deletions with high penetrance and association with multifocal dystonia and adult onset in a Taiwanese DRD population [37].…”
Section: Phenotype Correlations With Genotype or Biochemical Phenotypementioning
confidence: 99%
“…For PCDD, AR-GTPCHD, DHPRD, and PTPSD, there are no consistent reports on genotype-phenotype correlation. For AD-GTPCHD, there is certain heterogeneity: Some publications discuss and exclude genotypephenotype correlation [35,36]. Others describe different large heterozygous GCH1 deletions with high penetrance and association with multifocal dystonia and adult onset in a Taiwanese DRD population [37].…”
Section: Phenotype Correlations With Genotype or Biochemical Phenotypementioning
confidence: 99%
“…We reviewed a previous report and found that Arg249Ser, Ser81Pro, Ser76X, Gly203Arg, 249del A, and IVS5+3insT have been reported in Taiwan (Hwu, Chiou, Lai, & Lee, 2000;Wu-Chou et al, 2010). In a group of Chinese Han patients, the locus included Gly155Ser in exon 3 (Hu et al, 2011); Met137Arg in exon 2 (Hu et al, 2011); Gly203Arg in exon 5 (Hu et al, 2011;Liu et al, 2010;Yu, Zhou, Hu, & Xu, 2013); Cases within each family had either pure parkinsonism or dystonia with or without parkinsonism. Patients with uncertain sign or onset age were excluded.…”
Section: Discussionmentioning
confidence: 90%
“…Ala98Val (Cai et al, 2013); Ile135Thr (Cai et al, 2013); Leu91Val (Wu et al, 2008); Pro95Leu (Wu et al, 2008); Val204Gly (Wu et al, 2008) and 628delC (Wu et al, 2008); Met1Ile (Li et al, 2007); Thre94Met (Yu et al, 2013); Leu145Phe (Yu et al, 2013); and c. 453+6G>T (Yu et al, 2013). A study of 40 patients with Segawa disease suggested that most mutations in Chinese patients with Segawa disease are clustered in two regions-the 210-360 and 550-650 base pair (Yu et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the G66715314C mutation may have important effects on economic traits, and its association with chicken growth traits needs further study. Conversely, four SNPs found in this study were located near the exon-intron boundaries, which are special regions that usually had important functional roles in protein [ 50 ]. Three of these four SNPs were associated with growth traits.…”
Section: Discussionmentioning
confidence: 99%